Study on the Cracking Mechanism of Arch Foot of CFST Tied Arch Bridge Based on Multiscale Numerical Simulation - Zeying Yang; Changhao Cai; Zhilin Qu; Chenghe Wang; Yinglin Sun (Advances in Civil Engineering)
In order to study the causes of arch foot cracking, a multiscale numerical simulation method was used to establish the finite element model of Xizha Bridge during the construction stage of the Xiaoqing River restoration project in Jinan by using Midas Civil, and the internal forces under adverse conditions were extracted. On this basis, Abaqus was used to establish the local model of arch foot, and the plastic damage model parameters were introduced to conduct stress analysis. The results show that the anchorage stress of prestressed steel bundle is too high. On the one hand, the stress component produced by the bending of the prestressed steel bundle can squeeze the concrete inside the bending angle, and on the other hand, it will stretch the concrete outside the bending angle, resulting in concrete cracking. There is a tendency of relative displacement between arch rib and arch foot, and the interface surface of arch foot and arch rib is pulled by the displacement of arch rib, resulting in cracking. Arch foot inner bend produces a certain tensile stress, and if this place is not paid enough attention to, insufficient reinforcement will produce large cracks. Finally, it is suggested that concrete cracking can be avoided by arranging enough reinforcement bars under anchor and sealing reinforcement bars, encrypting steel mesh, arranging shear studs, and extending insertion depth.